PENDEKATAN TRADISIONAL DALAM TERMINOLOGI: SENI TENUN MELAYU - Mohd Bukhari, Nur Azimah; Abdul Wahid, Puteri Roslina; Samsudin, Nurul Haniza (Jurnal Pengajian Melayu (JOMAS), 2018)
Terminology is an important aspect of Malay language planning, especially Malay as a language of knowledge. This paper focuses on traditional approaches in coining of the Malay weaving art terminology. An art outcome was not born out of a vacuum, but was born out of the history of the civilization and the life of its support community (Anwar, 2008). This study is a descriptive qualitative research. The explanation of the concept of the term based on data, analogy, philosophy and the cognition of the Malay speakers. This shows the wisdom of the Malays in coining the Malay weaving terminology. Terminologist generates terms that represent the concept accurately. Therefore, this study shows that the Malay weaving terminology had achieved the standardization as suggested by Felber (1995) in the Terminology Manual. Keywords: terminology, Malay language, term, the art of weaving.